Risk of progression in patients with chronic atrophic gastritis: A retrospective study - Sun, Lu; Jin, Xiaoliang; Huang, Liang; Zhao, Jing; Jin, Haifeng; Chen, Mingtao; Zhang, Chunli; Lu, Bin (Frontiers in Oncology, 2022)
Background: Chronic atrophic gastritis (CAG) can progress to gastric cancer (GC) thus requiring endoscopic surveillance. Here, we analyze various aspects of CAG progression, time, and mucosal background, to guide reasonable surveillance. Methods: CAG patients with three or more endoscopies from 2010–2021 were included. All cases were analyzed for rate and time of progression, and cases with operative link on gastritis assessment (OLGA) staging, operative link on gastric intestinal metaplasia assessment (OLGIM) staging, and Kimura-Takemoto classification were further analyzed. Additional investigation of guideline-defined low-risk patients by reviewing endoscopy in the short-term (1–2 years) after baseline identified several patients as high-risk. Results: Ninety-seven (10.4%) of the 929 CAG patients progressed to low-grade intraepithelial neoplasia (LGIN), high-grade intraepithelial neoplasia (HGIN), or GC, during the observation period of 36–129 months (median 53, IQR=24), including 75 (8.1%) cases of LGIN, eight (0.9%) of HGIN, and 14 (1.5%) of GC. Among 170 patients with OLGA/OLGIM at baseline, two (2/2, 100%) GC cases occurred in patients with OLGA/OLGIM Ⅲ and Ⅳ. Of the 236 patients with Kimura-Takemoto classification at baseline, 5/7 (71.4%) cases of GC occurred in patients with C3–O3. Ten, 11, and 25 patients classified as low-risk on the European, British, and Chinese Guidelines, underwent additional endoscopy within 1–2 years, resulting in three (30.0%), four (36.4%), and eight (32.0%) patients being classified as high-risk on these guidelines, respectively. Conclusion: A minority of CAG patients can progress to GC. OLGA/OLGIM Ⅲ and Ⅳ staging are closely associated with progression. Disease-associated risk may be underestimated in one-third of patients classified as low-risk by initial endoscopy.